PKM KELOMPOK KADER DALAM DETEKSI DINI STUNTING MELALUI INTEGRASI APLIKASI WHATSAPP AUTO RESPONDING (WAR) DI POSYANDU DAHLIA DESA KABASIRAN - Irawan, Andi Muh Asrul; Rahmawati, Lusi Anindia; Cholidhazia, Putri; Alifia, Daiva; Nurrohmah, Nisa (Jurnal Abdi Insani, 2024)
Stunting is a condition of growth failure in children due to long-term malnutrition. The prevalence of stunting in Indonesia remains high, with reduction targets not yet achieved. Posyandu (integrated health service posts) and their cadres play a crucial role in efforts to reduce stunting cases through nutrition education and early detection. The aim of this community service activity was to improve the skills of cadres in measuring body length and height, which are then integrated with WhatsApp Auto Responding (WAR) for early stunting detection. The methods used include socialization, training on measuring nutritional status of toddlers, application of WAR technology, as well as program mentoring and evaluation. The activity was carried out at Posyandu Dahlia, Kabasiran Village, targeting 26 posyandu cadres in August 2024. The results of the activity show that there was a significant improvement in cadres' skills in anthropometric measurements and the use of WAR technology for stunting detection (p<0.05). Program evaluation indicates an increase in cadres' knowledge and skills in conducting measurements and early stunting detection. The conclusion of this activity was that empowering posyandu cadres through training and technology application can enhance the effectiveness of early stunting detection in the community, supporting efforts to reduce stunting prevalence at the posyandu level.